Sugars profiles of different chestnut (Castanea sativa Mill.) and almond (Prunus dulcis) cultivars by HPLC-RI - Barreira, João C.M. (2010)
Sugar profiles of different almond and chestnut cultivars were obtained by high-performance liquid chromatography (HPLC), by means of a refractive index (RI) detector. A solid-liquid extraction procedure was used in defatted and dried samples. The chromatographic separation was achieved using a Eurospher 100-5 NH2 column using an isocratic elution with acetonitrile/water (70:30, v/v) at a flow rate of 1.0 ml/min. All the compounds were separated in 16 min. The method was optimized and proved to be reproducible and accurate. Generally, more than 95% of sugars were identified for both matrixes. Sugars profiles were quite homogeneous for almond cultivars; sucrose was the main sugar (11.46±0.14 in Marcona to 22.23±0.59 in Ferragnes g/100 g of dried weight), followed by raffinose (0.71±0.05 in Ferraduel to 2.11±0.29 in Duro Italiano), glucose (0.42±0.12 in Pegarinhos two seeded to 1.47±0.19 in Ferragnes) and fructose (0.11±0.02 in Pegarinhos two seeded to 0.59±0.05 in Gloriette). Commercial cultivars proved to have higher sucrose contents, except in the case of Marcona. Nevertheless, chestnut cultivars revealed a high heterogeneity. Sucrose was the main sugar in Aveleira (22.05±1.48), Judia (23.30±0.83) and Longal (9.56± 0.91), while glucose was slightly prevalent in Boa Ventura (6.63±0.49). The observed variance could serve for intercultivar discrimination.